ANALISIS KINERJA KEUANGAN PADA PT GUDANG GARAM, TBK - Huntojungo, Febriani; Ferdinand Runtuwene, Roy; Keles, Dantje (Sam Ratulangi University, 2017)
Summary. The performance of the company's financial statements stable financial condition is seen in 2014 sales increased from year to year, ranging from 65% in 2012 to 66.8% in 2013 and reached 68% in 2014. While in 2015 Sales decreased Each by 0.5% to 60.9 billion cigarettes. The main question in this study is